Does Digital-Intelligence Contribute to Carbon Emission Reduction? New Insights from China - Jian Hou; Wei Kang; Yao Li; Shuming Liang; Shuaishuai Geng (SAGE Open)
Digital-intelligence plays an important role in transforming the energy consumption structure and promoting the emission reduction process. To explore the relationship between digital-intelligence and regional carbon emissions, we assume that there is a differential impact in carbon emission reduction effects, given the obvious differences in regional green technology innovation during the development of digital-intelligence in China. Thus, we systematically construct a new digital-intelligence system definition and include the heterogeneous threshold of green technology innovation in the relationship of the impact of digital-intelligence on carbon emissions by using a nonlinear dynamic threshold model. The results show that the development of regional digital-intelligence in China exhibits a relatively stable upward trend, and there is heterogeneity among regions. Interestingly, there is a significant heterogeneous threshold effect from green technology innovation between digital-intelligence and carbon emissions. A lower level of green technology innovation will increase the carbon emission effect of digital-intelligence to a certain extent, but when green technology innovation increases and exceeds a threshold, digital-intelligence is able to dramatically inhibit regional carbon emissions. Our research answers the question of how to achieve digital-intelligence transformation through green technology innovation and reduce total regional carbon emissions and provides new insights for developing countries to curb carbon emissions.